PENERAPAN ETIKA PROFESIONAL DALAM PELAYANAN INFORMASI CUACA : BMKG MARITIM TANJUNG PERAK SURABAYA - Anwar, Sagita Suryani; Ilham, Ilham (Journal of Information System, Applied, Management, Accounting and Research, 2026)
This article discusses the application of professional ethics in the context of maritime weather information services provided by BMKG Maritim Tanjung Perak Surabaya. The study focuses on ethical aspects in delivering accurate, timely, and accessible information to the maritime community. The methodology includes literature review and analysis of the implementation of professional ethics in practice. The results show that BMKG Maritim Tanjung Perak has applied principles of professional ethics such as accuracy, timeliness, accessibility, transparency, and integrity in its services, despite facing various challenges. Continuous improvement efforts are made through personnel capacity development, system modernization, governance strengthening, and stakeholder collaboration. A case study on the handling of extreme weather information in January 2023 demonstrates the effectiveness of the application of professional ethics, which has a significant impact on the safety of the maritime community.